1984
DOI: 10.1002/mpo.2950120402
|View full text |Cite
|
Sign up to set email alerts
|

Effective chemotherapy for metastatic malignant sacrococcygeal tumour

Abstract: Two children with disseminated malignant sacrococcygeal tumour were treated with six courses of vinblastine, cis-platinum, and bleomycin. Both had exploratory operations after four courses of treatment and no histological evidence of malignant disease was found. The two children have remained free of disease with normal alpha-fetoprotein levels for 30 months and 18 months, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…There were no recurrences in the respondent population. The median age of respondent was 16.7 years (range 3-29) and the median size of the tumor was 7 cm (range [3][4][5][6][7][8][9][10][11][12][13][14]. Eleven out of the 14 patients reported having twins in their family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no recurrences in the respondent population. The median age of respondent was 16.7 years (range 3-29) and the median size of the tumor was 7 cm (range [3][4][5][6][7][8][9][10][11][12][13][14]. Eleven out of the 14 patients reported having twins in their family.…”
Section: Resultsmentioning
confidence: 99%
“…The mortality and morbidity associated with prenatal SCT are often attributed to preterm delivery and to complications such as tumor hemorrhage, umbilical flow obstruction, high output cardiac failure, hydrops fetalis and bladder outlet obstruction [5][6][7]. Prognosis for SCT has improved in recent years due to prenatal diagnosis, as well as the use of multi-agent chemotherapy protocols for those with malignant histology [8,9] The current management of SCT depends on gestational age, the vascularity of the tumor and the presence of associated anomalies. The treatment of choice for SCT is early surgical resection including complete excision of the coccyx.…”
Section: Introductionmentioning
confidence: 99%
“…Seven patients had low-stage tumor (I or ll) and four had advanced-stage tumor (111 or IV). Three of six evaluable patients attained a complete response at 21 weeks. The three patients with a residual soft tissue mass at restaging underwent further therapy.…”
Section: Treatment Of Endodermal Sinus Tumor In Children Using a Regimenmentioning
confidence: 97%
“…There is evidence, however, that this chemotherapeutic regimen is associated with more toxicity and even treatment induced mortality in children [2,3,5,12] as compared to the fairly satisfactory tolerance in adults. According to some reports approximately half of the children so treated developed pul monary fibrosis with lethal outcome [2,5] so that it was concluded that further use of bleomycin in children is to be abolished [2], or at least the combination of cis-platinum and bleomycin is to be avoided [1],…”
Section: Ovarialtumoren -Keimzelltumoren -Bleomycin Bei Kindernteratomementioning
confidence: 99%
“…Fully malignant germ cell tumors with the exception of immature teratomas and seminomas/ dysgerminomas have been associated with a poor outcome of less than 10% cure rate despite radical surgery, radiation and chemotherapy with vincristine (VCR), actinomycin D (AMD), and cyclophosphamide (CYC) [9,10,13]. The combi nation of vinblastine (VBL), bleomycin (BLEO) and cisplatinum (DDP) has improved the prognosis for testicular tumors in adults and also in children [2,8,11]. There is evidence, however, that this chemotherapeutic regimen is associated with more toxicity and even treatment induced mortality in children [2,3,5,12] as compared to the fairly satisfactory tolerance in adults.…”
Section: Ovarialtumoren -Keimzelltumoren -Bleomycin Bei Kindernteratomementioning
confidence: 99%